“FIZIKA OQÍTÍW METODIKASÍ” PÁNINEN LABORATORIYA ShINIǴIWLARÍNA INTERAKTIV TEXNOLOGIYALARDÍ QOLLANÍW - Karlıbaeva, G.E. (SCIENCE and SOCIETY, 2025)
The article presents ideas for introducing interactive technologies into laboratory work in the subject “Methods of Teaching Physics” with the aim of improving the effectiveness of teaching. It is also based on the assumption that the task of increasing the creative and experimental activity of students can be solved by using laboratory work to reinforce theoretical knowledge. Information is provided on the methodology for implementing the “Scarab” method for the laboratory work “Studying the conditions of equilibrium of bodies” in the subject “Methods of Teaching Physics”.